Pengaruh Kompetensi terhadap Kinerja Guru Sekolah Dasar Negeri di Kota Makassar - Nur Aeni; Nur Naninsih; Mattalatta Mattalatta; Ansar Ansar; Kurniawaty Sandra (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2024)
This study aims to investigate the influence of competence on teachers' performance in public elementary schools in Makassar City. The methodology employed combines descriptive and confirmatory approaches, which provide a clear depiction of the data and test the influence of identified variables, including discipline, competence, leadership, motivation, and teacher performance. The research is conducted in 58 schools across three districts in Makassar, with the research period planned for three months, from April to July 2024. The results indicate that although leadership has a positive influence on teacher performance, the impact is not significant. This finding suggests that factors such as the school environment and resource limitations can affect the effectiveness of leadership in enhancing performance. This study provides important insights for developing educational policies that better support improving teacher performance at the elementary level.